Slope classification of Slovenia and selected field survey results from the Slovenian Motorway Project: A dataset for studying the influence of geomorphic processes on the field survey's site discovery effectiveness (Data paper) - Luka Gruškovnjak (Internet Archaeology)
This data paper concerns a dataset of slope classification results for the entire country of Slovenia and data on extensive and intensive survey results at 24 case study sites along with excavated areas at the sites.